Realização e interpretação de ensaios de um protótipo do piezocone torpedo - Pinheiro, Arthur Veiga Silvério (2019)
Three series of torpedo-piezocone tests, performed at the Sarapuí II soft clay test site in 2009, 2013 and 2014 have been analysed. Problems and solutions related to the data acquisition system and the maintenance of saturation of the filters, have been presented and discussed. Impact velocity were in the range 3,07 m/s - 9,40 m/s (150 to 470 times the rate of conventional piezocone tests, 20 mm/s), for fall heights between 0,38 m and 4,38 m. The velocity still increased inside the soil, before reducing and eventually stop in soil layers beneath the soft clay. The combination of the measurements from the various transducers, especially acceleration, cone resistance and pore pressure, allows a clear perception of the penetration mechanism into the soil. The determination of equilibrium pore pressure, from dissipation tests, was proven to be a valuable tool for the determination of the maximum depth reached by the penetrometer. Cone resistance and sleeve friction were very much affected by the velocity, with respect to the regular penetration rate of 20 mm/ from the conventional test. The rate effect is more pronounced in the case of the sleeve friction. Rate effect was also noticed in the pore pressures u1 and u2, more significantly in u2. A method to estimate the penetration forces on the penetrometer, during penetration, based on the penetrometer geometry, the cone resistance and the sleeve friction, was proposed. The undrained shear strength was properly estimated from the torpedo-piezocone, based on a calibration with regular piezocone tests.